ANALISIS MISKONSEPSI KETERAMPILAN MEMBACA PADA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Anita Widyastuti; Retno Winarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading ability is a basic skill that must be mastered by elementary school students to support learning success. However, in practice, misconceptions are still found in students related to reading comprehension, which is often misinterpreted as just pronouncing texts. This study aims to identify forms of misconceptions in reading skills of grade IV elementary school students, analyze the causes, and formulate improvement strategies. This study uses a descriptive qualitative approach with subjects of grade IV students and class teachers at SDN 2 Pagutan. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed that students experienced misconceptions in understanding the nature of reading, such as difficulty in determining the main idea, answering questions only literally, and being unable to distinguish between facts and opinions in the text. Factors causing misconceptions include the teacher's learning approach which is still technical, the minimal use of varied learning media, and practice questions that do not stimulate critical understanding. Therefore, it is necessary to improve reading learning strategies that are more meaningful and dialogical, accompanied by gradual guidance so that students are able to become active and reflective readers.